Políticas e ações de formação continuada propostas pela Secretaria de Educação do município de Três Lagoas, MS: A análise dos(as) coordenadores(as) que atuam nos anos iniciais do ensino fundamental – ciclo de alfabetização - Andrade, Angela Bezerra dos Santos (2022)
The study's subject of this research is related to public and continued training of teachers, proposed for the Secretaria Municipal de Educação e Cultura (SEMEC), of the Três Lagoas– MS. The main objective was to analyze comprehension, of the technical coordinators in SEMEC and the coordinators who work with the initial students at Elementary School (literacy years) in the municipal network of Três Lagoas, about the importance and usefulness of continuing teachers’ training policies in the municipality in the last five years. The research investigation was conducted in three stages: bibliographical and documentary, field survey and organization, and analysis of results. The bibliographic and documentary stage covered surveys in the indexing bases of national scientific production, surveys of normative acts and legislation related to the main policies of continuing education of teachers in Brazil and in the Municipality of Três Lagoas. In the field survey stage, two focus groups were carried out according to the guidelines of Berenger, Elliot and Parreira (2012), using discussion scripts: (1) the SEMEC technicians; (2) coordinating teachers and educational specialists whose work in the early years of Elementary School and, for that, was used an on-line questionnaire, which preceded the focus groups to profile the participants. The meetings of the focus groups were through the Google Meet platform, recorded and later transcribed, equipped with codifications guided by the theories of Pretti (1999). Through the content analysis of Bardin (2016) we analyze the information obtained by the investigation. Based on the definitions of the National Education Plan (PNE) applicable from 2014 to 2024, it was understood that, in the normative scope, educational policies aim to promote the continuing education of teachers, focusing on the quality of education and valuing the work of teachers. The theoretical reflections provided by Gatti (2008, 2021), Freitas (1992, 2012, 2014), Imbernón (2004, 2010), Libâneo (2004, 2015), Scheibe (2010), among other authors who were essential for the discussion of the theme. In this investigation, the conception of State was taken in the sense of Gramsci’s Integral State (2007). The analyzes made possible to verify that the participants consider the continuing teacher's training policies useful and important, because SEMEC has valued this important continuing education in the manutention institutions themselves and has been propitiating the beginning of a new training culture. However, gaps were observed in the knowledge of the participating coordinators in relation to the goals proposed in the PNE to conduct studies at the stricto sensu level. We notice in this study the inducing role of the Brazilian State influencing the policies of continued training of teachers and its compliance in the Municipal Network of Three Ponds. Keywords: Continued training of teachers’ policies. Pedagogical coordination. the early years of Elementary School. Municipal Education Network.